PENGARUH SENAM ERGONOMIK TERHADAP PENURUNAN TEKANAN DARAH PADA LANSIA YANG MENGALAMI HIPERTENSI - Ananda D. Thei (CHMK Applied Science Journal, 2018)
Being old or getting old is a state that occurs in human life. Being old is one of the factors that cause hypertension, this is due to the increasing age of declining body function is characterized by decreased elasticity of arteries and blood vessel stiffness so vulnerable to increased blood pressure in the elderly. One of the complementary therapies that can be used to lower blood pressure is by ergonomic exercise. This research aims to determine the impact of ergonomic exercise on the decrease in blood pressure in elderly people who have hypertension In UPT Panti Sosial Penyantun Budi Agung Kota Kupang. The research used Pra Experimental design: one group pretest-postest with Cross Sectional approach. The sample was selected by total sampling technique with 30 respondents. The ergonomic exercise intervention is done one week for 3 times. Before gymnastics, blood pressure pre-test and ergonomic exercises were administered and followed by post test blood pressure measurement. The result of statistical test using paired sample t test obtained p value = 0.000 smaller than α value (0,05) this result show there is influence of ergonomic gym to decrease blood pressure in elderly who have hypertension In UPT Panti Sosial Penyantun Budi Agung Kota Kupang. So researchers suggest that ergonomic gymnastics interventions can be used as one of complementary therapies in elderly who have hypertension. Keywords: ergonomic gymnastics, elderly, hypertension.